2018
DOI: 10.1590/s1980-6574201800010003
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of recovery, external and internal load by playing position and match outcome in professional soccer

Abstract: Aimsː To compare the internal and external load and the recovery by playing position and the match outcome (wins, losses or draws) in professional soccer. Methodsː Twenty-three male professional soccer athletes from a team of the first division of the Brazilian Championship took part into the study (age 26.1 ± 3.8 years old, weight 77.5 ± 5.0 kg, height 177.6 ± 5.1 cm). During the games, athletes were monitored by GPS and the variables of external loads were taken. Additionally, the session rating of perceived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 15 publications
2
5
1
Order By: Relevance
“…In opposition to our data, Conde et al [19] found no difference on recovery measured 40 h40 hours after the matches by perceived recovery scale. Although our study did not use the same scale, we speculate that we could obtain different results in MD+1.…”
Section: Comparison Of Match Day Minus For Tl Data Between Wins Vs Draws; Wins Vs Defeats; and Draws Vs Defeats For Squad Averagecontrasting
confidence: 99%
See 1 more Smart Citation
“…In opposition to our data, Conde et al [19] found no difference on recovery measured 40 h40 hours after the matches by perceived recovery scale. Although our study did not use the same scale, we speculate that we could obtain different results in MD+1.…”
Section: Comparison Of Match Day Minus For Tl Data Between Wins Vs Draws; Wins Vs Defeats; and Draws Vs Defeats For Squad Averagecontrasting
confidence: 99%
“…To the best of our knowledge, only one study has tried to understand if there is any difference between the results of a soccer match (win, draw and defeat) for the internal training load of elite professional players [18] and one regarding internal and external TL combined [4], but none with relation to the match result situation, simultaneously. In order to reach a better sport approach, the match result may influence the external and internal TL applied and vice-versa [19]. We consider it is crucial to understand whether the periodization of the internal and external TL of the microcycles throughout the in-season influences the performance of the players through match result (win, draw or defeat).…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the playing positions, no differences were found in the perceived load variables in the competitive match. These findings are consistent with what has been found in previous studies during matches with nondisabled professional football players [44,45]. However, other studies reported differences according to the perceived load exertion and playing position during competitive matches [24,25,46].…”
Section: Discussionsupporting
confidence: 93%
“…Concerning high-intensity requirements, athletes perform between 150 and 250 actions between 15 and 20 m, representing about 30% of the total match duration [ 9 ]. In addition, the total distance covered by players in sprints usually comprises between 5 and 10% of the total distance covered [ 9 , 10 ], with a frequency of one action every 90 s [ 9 ].…”
Section: Introductionmentioning
confidence: 99%